The technological approach to organization of training process of gymnasts at a stage of initial sports specialization by the example of mastering of main exercises - Shlyakhtov, V.; Semenov, D. (World Congress of Performance Analysis of Sport VIII, 2008)
Good basic skills (hand-stand, dynamic posture and push-off) made the most contribution into the quality of the performance of the main exercises mastered during the investigation. The score for the performance of the main exercises increased in average by over 0,9 points. The received results confirm the idea that base skills are a basis for performance of the main exercises in gymnastics. The results of the research give a clear comprehension of gymnasts` technique training process and the mechanism of locomotor actions performance. The pedagogical investigation data certify evident differences between the control and experimental groups. It proves efficiency of the developed technological approach to the gymnasts` training process.